Is This Part Substantial or Is It Time to Rethink the Concept of Originality in Music? - Salsalina Itha Karina (Faculty of Law, Andalas University, 2022)
The vagueness in the concept of originality in music has been problematic, especially relating to the enforcement of copyright. There is no definite line between ideas and the expression of an idea, which is essentially the object of copyright in music. The act of using a general concept in music could be mistaken as substantial taking and even futher a copyright infringement. The purpose of this article is to give a new perspective on the concept of originality in music, specifically in determining the act of substantial taking, and to explain why it could be time to finally rethink this concept. The research shows that the concept of substantial taking, as regulated by is Copyright Act, could hardly be applied to music due to the vagueness in the concept of originality. This reflects the necessity of a standardization for originality in music, which could be achieved through dialogues between musicologists, musicians, and other relevant professionals.